Use of Neutrosophic Cognitive Maps for the Analysis of Five Didactic Options for Instruction in the Numerical and Research Skills of Accounting Students - Davila, Jose A. Orb; Vela, Rilke Chong; Leon, Tomas F. Rosales; Huaman, Castillo Gina M; Reategui-Paredes, Victor R (Neutrosophic sets and systems, 2024)
This article explores the innovative use of Neutrosophic Cognitive Maps to evaluate and compare five teaching approaches aimed at improving numerical and research skills among accounting students. This methodology, which integrates elements of neutrosophic theory, allows us to capture the inherent uncertainty and ambiguities in the perception and evaluation of educational options. Through a detailed and systematic analysis, the strengths and limitations of each approach are examined, highlighting how Neutrosophic Cognitive Maps offer a robust conceptual structure for discerning between the subtle complexities that affect effective learning. The results reveal profound elements about how different teaching strategies can influence the acquisition of key competencies in accounting. From the integration of advanced technologies to more traditional methods focused on conceptual development, each approach is evaluated not only for its surface effectiveness, but also for its ability to adapt to the cognitive and emotional diversity of students. This multidimensional approach underscores the importance of considering not only quantitative results, but also the underlying processes and subjective perceptions that shape the educational experience, offering a comprehensive framework for continually improving teaching in de-manding and dynamic academic environments. Keywords: Didactic Approaches, Neutrosophic Cognitive Map, Neutrosophic Number, Neutrosophic Graph, Hidden Patterns.